Study protocol and baseline characteristics of SCHOOL IN ACTION program on support to physical activity and healthy lifestyles in adolescents - Silva dos Santos, Sueyla Ferreira da; Bordin, Drenya [UNESP]; Dornelas de Souza, Elaine Fernanda; Freitas Junior, Ismael Forte [UNESP] (Elsevier B.V., 2020)
Physical activity promotes positive effects on people's health, but most adolescents do not engage in sufficient physical activity to receive the benefits. Studies suggest that school-based interventions can be effective in increasing physical activity in adolescents. However, the literature is inconsistent on the effect size and the type of intervention. This paper presents the design of the SCHOOL IN ACTION program to increase physical activity engagement and healthy eating habits. The cluster randomized controlled trial was performed during a period of six months of intervention and 12 months of follow-up in adolescents from four Brazilian public schools. The theoretical model is based on health promoting schools and the social-ecological and self-determination theory. The action strategies were: improvement of exercises intensity during physical education classes and during lunch breaks; vegetable gardening experience; active breaks in non-physical education classes; counselling health to parents and adolescents and changes in the school environment to promote physical activity and healthy eating. Primary variables were physical activity and sedentary behavior (both assessed by accelerometers). Secondary variables were body composition (assessed by dual-energy x-ray absorptiometry) and eating habits (assessed by questionnaire and 3-day food recall). Questionnaires were used to assess other information related to life satisfaction, health behavior and socioeconomic information. Statistical analysis will follow the principles of intention-to-treat and will explore the composition data analysis and mediating factors of lifestyle-related behaviors. We propose that SCHOOL IN ACTION program will be effective to provide evidence to increase physical activity and food healthy habits in adolescents' students.
Keywords: Physical activity; School-based intervention; Lifestyle; Sedentary behavior; Adolescent; Mixed methods